Tradycja i nowoczesność w formułach powitań i pożegnań na przykładzie języka mówionego mieszkańców gminy Zadzim = Tradition and modernity in greetings and farewells` formulas on the example of spoken language of the municipality of Zadzim`s residents - Woźniak-Wrzesińska, Ewelina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author of the text analyses the formulas of greetings and farewells considering the origin, age and gender of the observed language users. The field of observations covered a small locality, due to the absence of dynamic language changes in the small rural sites. Using passive methods of research, the author presents the coexistence of traditional and modern formulas of greetings and farewells.
Keywords: język mówiony; powitania i pożegnania; tradycja; nowoczesność; obyczaje; zmiana; spoken language; greetings and farewells; tradition; modernity; custom; change